COOPERAÇÃO ENTRE AGENTES PÚBLICOS E PRIVADOS PARA DESENVOLVIMENTO DE INOVAÇÃO NO TURISMO SUSTENTÁVEL: UM ESTUDO NO MUNICÍPIO DE PRUDENTÓPOLIS-PR - Kotzko, Ana Maria (2019)
This study aimed to understand the process of cooperation between public and private agents for the development of innovation in sustainable tourism in the municipality of Prudentópolis-PR. We sought to characterize the main motivations for interorganizational cooperation from the perception of public and private agents of the city of Prudentópolis-PR; list the main facilitators, impediments and results of interorganizational cooperation for the development of sustainable tourism in the municipality of Prudentópolis-PR; and evaluate innovation in sustainable tourism as inducer or result of interorganizational cooperation in the city of Prudentópolis-PR. The methodology used the qualitative research of descriptive and analytical nature and cross-sectional case study as a research strategy. Data collection occurred through documentary research, direct observation, field diary and semi-structured interviews with fifteen representatives of the public and private sector participating in the Municipal Tourism Council of Prudentópolis-PR. For the analysis, we used content analysis. and data triangulation as techniques for inferring and interpreting the collected data. The research results are evidenced from the antecedents, facilitators, hinders, results and questions related to innovation in interorganizational relations present in the tourism sector of Prudentópolis-PR. The antecedents demonstrate the aspects based on the desire to cooperate need, power/authority, legitimacy, efficiency and reciprocity as motivations for organizations to establish cooperative relations in tourism. The facilitators are related to trust, commitment, collectivity, planning and organization of tourism activities as a way of maintaining cooperation between public and private agents of the municipality. Concerning the obstacles, mainly based on distrust, opportunism, rivalry between partners and managerial complexity are revealed as obstacles to the continuity of tourism cooperation. Regarding the resulting aspects found in organizations and in the municipality, efficiency in activities, market stability, and increased legitimacy are beneficial results for organizations. Social, economic, environmental and political issues contribute to the development of sustainable tourism in the municipality. Innovation as an inducer of cooperation is based on the pursuit of new product development, learning and knowledge exchange as main motivations for interorganizational cooperation in tourism. Lastly, innovation as a result of cooperation comes from the emergence or improvements in products and processes, as well as managerial, marketing and institutional innovations. It is concluded that the cooperation process established in Prudentópolis-PR, provides improvements for organizations and the tourism sector of the municipality. From this, it is considered that innovation can be considered as either inducer or result of the process of interorganizational cooperation in tourism of the municipality, contributing to the sustainable development of the region.